ARGINASE AND ORNITHINE CARBAMOYL TRANSFERASE ACTIVITY AND UREA ACCUMULATION DYNAMICS IN DIFFERENT PHASES OF PLEUROTUS OSTREATUS (JACQ.:FR.) KUMM. FUNGI FRUCTIFICATION (Proceedings of the YSU B: Chemical and Biological Sciences, 2014)
Two enzymes of the ornithine cycle (ornitine carbamoyl transferase and arginase) activities and urea accumulation dynamics of being wood decaying and food product fungi Pleurotus ostreatus (Jacq.:Fr.) Kumm. during aging and developing different phases were investigated. Concomitant to fungi development and growth, arginase activity and positive dynamics of urea are connected for providing the corresponding level of osmotic pressure in hymenium.
Keywords: Pleurotus ostreatus, pure culture, fruit body, arginase, ornithine carbamoyl transferase